Ultrathin transparent Copper(I) oxide films grown by plasma-enhanced atomic layer deposition for Back-end-of-line p-Type transistors. (10th June 2021) - Bae, Hagyoul; Charnas, Adam; Chung, Wonil; Si, Mengwei; Lyu, Xiao; Sun, Xing; Park, Joon; Wang, Haiyan; Zemlyanov, Dmitry; Ye, Peide D
Abstract: We demonstrate p-type thin-film transistors (TFTs) on copper(I) oxide (Cu2 O) grown by plasma-enhanced atomic layer deposition (PEALD) with bis(N, N′-di-sec-butylacetami-dinato)dicopper(I) as the Cu precursor and oxygen (O2 ) plasma as an oxidant. PEALD provides many if the advantages of other ALD processes, including uniformity and conformality, but with the additional ability to actively generate reactants and to add substantial energy from the plasma which may be important in defect control, low-temperature deposition. In this letter, Cu2 O films were grown on SiO2 /Si substrates under different substrate temperatures (160 ∼ 240 °C) and post-deposition annealing was carried out under various temperatures (300 ∼ 1100 °C) to improve the growth rate and crystallinity of the Cu2 O films. The fabricated p-channel bottom-gate Cu2 O transistors with a controlled thickness of 12 nm have high transparency over 90% and exhibit a subgap density of states ( g ( E )) of 7.2 × 10 18 eV −1 ·cm −3 near the valence band ( E V ), contact resistivity ( R C ) of 14 kΩ·mm, I ON / I OFF ratio of 2 × 10 3, and field-effect mobility of 0.1 cm 2 /V·s.